(untitled) (Research, Society and Development, 2020)
Considering the current world context of social isolation, this research was developed from data collected from 6 elderly people, men and women between 60 and 90 years old, who were discovered in a semi-structured interview that addressed questions about the experience of isolation in times of COVID-19, social network and feeling of loneliness. This study aimed to find out how an elderly person is adjusting to that moment, and how they have been conducting their feelings through the perspective of the feeling of loneliness. According to the data collected, we found that the phenomenon of loneliness presents itself in different ways, and generally translated the types of relationships we establish with ourselves, the other and the environment. In the current scenario, loneliness has been desired as a recurring and growing experience due to the social isolation caused by the pandemic that the world is going through, so that dealing with this event has become a more challenging task, considering that, being alone today has not always been a choice, but a necessity as a preventive measure.